1999
DOI: 10.1111/j.1749-6632.1999.tb07683.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Matrix Metalloproteinase Inhibition on Progression of Atherosclerosis and Aneurysm in LDL Receptor‐Deficient Mice Overexpressing MMP‐3, MMP‐12, and MMP‐13 and on Restenosis in Rats after Balloon Injury

Abstract: The broad-spectrum MMP inhibitor CGS 27023A was tested to determine its potential as a therapy for atherosclerosis, aneurysm, and restenosis. LDL receptor-deficient (LDLr -/-) mice fed a high-fat, cholic acid-enriched diet for 16 weeks developed advanced aortic atherosclerosis with destruction of elastic lamina and ectasia in the media underlying complex plaques. Lesion formation correlated with a 4.6- to 21.7-fold increase in MMP-3, -12, and -13 expression. Treatment with CGS 27023A (p.o., b.i.d. at 50 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 26 publications
5
117
1
3
Order By: Relevance
“…Temporal gene expression profiles in a rat carotid artery injury model showed a tight regulation of MMP expression and genes that modulate MMP expression [63]. This time window is also reflected by the results of the above-mentioned MMP inhibition study, in which decreased early neo-intima formation had no long-term effect [62]. In a mouse carotid ligation model, MMP-9 deficiency decreased intimal hyperplasia, reduced the late lumen loss, and led to a significant accumulation of interstitial collagen [64].…”
Section: S Heeneman Et Almentioning
confidence: 82%
See 3 more Smart Citations
“…Temporal gene expression profiles in a rat carotid artery injury model showed a tight regulation of MMP expression and genes that modulate MMP expression [63]. This time window is also reflected by the results of the above-mentioned MMP inhibition study, in which decreased early neo-intima formation had no long-term effect [62]. In a mouse carotid ligation model, MMP-9 deficiency decreased intimal hyperplasia, reduced the late lumen loss, and led to a significant accumulation of interstitial collagen [64].…”
Section: S Heeneman Et Almentioning
confidence: 82%
“…Inhibition of MMPs by either a synthetic MMP inhibitor or overexpression of TIMPs decreases neo-intima formation. One MMP inhibition study showed a decrease in early neo-intima formation, while long-term effects were not observed [62]. Temporal gene expression profiles in a rat carotid artery injury model showed a tight regulation of MMP expression and genes that modulate MMP expression [63].…”
Section: S Heeneman Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Вовлечение системы матриксных металло-протеиназ в процесс заживления раны после баллонного повреждения доказывает и тот факт, что увеличение экспрессии ингибитора ММп -тiМр-1 подавляет развитие неоин-тимы [146], в то время как у мышей с дефи-цитом тiМр-1 образование неоинтимы после электрического повреждения бедренной арте-рии было более выраженным. использование различных ингибиторов ММп приводило к Biochemistry aNd BiotechNology for moderN mediciNe замедлению образования неоинтимы и по-давлению миграции гладкомышечных клеток [147]. известно также, что между фибриноли-тической системой (системой активаторы плаз-миногена-плазмин) и системой матриксных металлопротеиназ существует тесное функцио-нальное взаимодействие [139,144].…”
Section: рис 8 схема механизмов способствующих пролиферации клетокunclassified